Detrimental role of prolonged sleep deprivation on adult neurogenesis - Fernandes, Carina; Rocha, Nuno Barbosa F.; Rocha, Susana; Herrera-Solís, Andrea; Salas-Pacheco, José; García-García, Fabio; Murillo-Rodríguez, Eric; Yuan, Ti-Fei; Machado, Sergio; Arias-Carrión, Oscar (Frontiers in Cellular Neuroscience, 2015)
Adult mammalian brains continuously generate new neurons, a phenomenon called neurogenesis. Both environmental stimuli and endogenous factors are important regulators of neurogenesis. Sleep has an important role in normal brain physiology and its disturbance causes very stressful conditions, which disrupt normal brain physiology. Recently, an influence of sleep in adult neurogenesis has been established, mainly based on sleep deprivation studies. This review provides an overview on how rhythms and sleep cycles regulate hippocampal and subventricular zone neurogenesis, discussing some potential underlying mechanisms. In addition, our review highlights some interacting points between sleep and neurogenesis in brain function, such as learning, memory and mood states, and provides some insights on the effects of antidepressants and hypnotic drugs on neurogenesis.